2021
DOI: 10.3390/ijerph18084327
|View full text |Cite
|
Sign up to set email alerts
|

Ticket to Ride: A Longitudinal Journey to Health and Work-Attendance in the JD-R Model

Abstract: The present study addresses one of the limitations of the JD-R model, namely, that analyses of the outcomes of the motivational process have largely focused on organizational outcomes and have neglected to investigate the associations between job resources, work engagement and health-related outcomes. Specifically, the aim of this paper is to show that health-related indicators may be outcomes of the motivational process in the job demands-resources (JD-R) model. We achieve this through a two-wave panel study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Our results indicate that there is still a strong necessity for longitudinal studies on the association between work engagement on health to investigate reciprocal effects. In light of our results and the examination of past evidence, we feel that the statement “engaged workers experience good health” (Langseth‐Eide & Vittersø, 2021, p. 10) could also be rephrased to state that employees who are in good health also experience higher work engagement. Although we do not deny the potential health‐improving effects of work engagement, it is important to investigate the causal relationships further and carefully consider the causality directions when planning and evaluating interventions to increase work engagement.…”
Section: Discussionmentioning
confidence: 63%
“…Our results indicate that there is still a strong necessity for longitudinal studies on the association between work engagement on health to investigate reciprocal effects. In light of our results and the examination of past evidence, we feel that the statement “engaged workers experience good health” (Langseth‐Eide & Vittersø, 2021, p. 10) could also be rephrased to state that employees who are in good health also experience higher work engagement. Although we do not deny the potential health‐improving effects of work engagement, it is important to investigate the causal relationships further and carefully consider the causality directions when planning and evaluating interventions to increase work engagement.…”
Section: Discussionmentioning
confidence: 63%
“…Previous literature on work engagement suggests that engaged workers perform better because work engagement is associated with better health (Bakker & Demerouti, 2008;Langseth-Eide & Vittersø, 2021). Our results indicate that there is still a strong necessity for longitudinal studies on the association between work engagement on health to investigate reciprocal effects.…”
Section: Theoretical Implicationsmentioning
confidence: 69%
“…Support for this hypothesis offers overall support for the application of JD-R theory to the health domain-thus, confirming our proposed HD-R framework. Moreover, whereas health factors in previous research have been modelled as outcome measures (e.g., Brauchli et al, 2015;Langseth-Eide & Vittersø, 2021), our study proposed and found that health factors can function as demands and resources as well. Taken together, our investigation adds to prior work-related research by expanding key JD-R concepts and processes to domains outside of work (e.g., Lesener et al, 2020;Martin, Collie, & Malmberg, 2023;Martin et al, 2021;Martin, Ginns, & Collie, 2023;Salmela-Aro et al, 2022).…”
Section: Findings Of Particular Notementioning
confidence: 78%
“…Although they found support for this expansion, their study was still focused on job demands and resources (not health demands and resources) and how these affected employees' health. Likewise, Langseth‐Eide and Vittersø (2021) investigated health (general health and sick leave) among employees and confirmed the JD‐R process, but once more, the demands and resources were work‐related, not health‐related. There are also applications of JD‐R theory to health settings (e.g., Kaiser et al., 2020; Meirun et al., 2020; Udushirinwa et al., 2023; Viotti et al., 2015), but these are focused on health care workers and how job (not health) demands and resources affect their workplace functioning.…”
Section: Demands and Resourcesmentioning
confidence: 92%